Transcriptomics in Health and Disease - Passos, Geraldo A. (Springer International Publishing : Imprint: Springer, 2014)
After sequencing the human genome a decade ago, researchers have continued their projects, but now to try to better understand how, and when, genes are expressed in health and disease. Efforts have been concentrated on the measurement of the expression of RNA transcripts. In an analogy to the genome, the term "transcriptome" was created to refer to the complete set of RNAs in a cell type or tissue in a particular situation. Transcriptomics is the science that studies this issue and it is a branch of functional genomics. Transcriptomics in Heath and Disease provides a comprehensive overview of the science of transcriptomics initially in health, focusing on the concept of the transcriptome and the main methods to evaluate it. The authors discuss the concept and use of gene expression signatures and transcriptional biomarkers in normal development and diseased tissues and organs. As the transcriptome changes depending on the pathology, there is also a focus on the variations in the gene expression in different diseases such as autoimmune, inflammation, cancer and infections. This book should be very useful for researchers in molecular biology focusing on gene expression, human genetics, immunology, and genomics.